Myosin forces remodel F-actin for mechanosensitive protein recognition - Ayala G. Carl; Matthew J. Reynolds; Xiaoyu Sun; Pinar S. Gurel; Donovan Y. Z. Phua; Keith Hamilton; Lin Mei; John W. Watters; Yasuharu Takagi; Alex J. Noble; James R. Sellers; Gregory M. Alushin (Nature, 2026)
Abstract Cells interface mechanically with their surroundings through cytoskeleton-linked adhesions 1,2 , which enable them to sense physical cues that instruct development and drive diseases such as cancer 3–5 . Contractile forces generated by myosin motor proteins 6,7 mediate these mechanical signal transduction processes through unknown protein structural mechanisms. Here we show that force generated by myosin elicits structural changes in actin filaments (F-actin) that modulate binding by the mechanosensitive adhesion protein α-catenin 8 . Using correlative cryo-fluorescence microscopy and cryo-electron tomography, we identify F-actin featuring sinusoidal regions of nanoscale oscillating curvature at cytoskeleton–adhesion interfaces enriched in zyxin, a marker of actin–myosin-generated traction forces 9 . We introduce a reconstitution system for visualizing F-actin in the presence of myosin forces using cryo-electron microscopy, which reveals morphologically similar F-actin supercoils. In simulations, compressive forces that mimic myosin activity produce supercoils, which can be generated by ensembles of asynchronous motors regardless of their directionality. Three-dimensional reconstruction of supercoils uncovers extensive asymmetric remodelling of the helical lattice of F-actin. This is recognized by α-catenin, which binds cooperatively along individual strands, preferentially engaging interfaces that feature extended inter-subunit distances while simultaneously suppressing rotational deviations to regularize the lattice. In sum, we find that myosin forces can deform F-actin, generating a conformational landscape that is detected and reciprocally modulated by a mechanosensitive protein, providing a direct structural glimpse at active force transduction through the cytoskeleton.